Inhibition of the Na+-glucose transporter SGLT2 reduces glucose uptake and IFNγ release from activated human CD4+ T cells - Jin, Zhe; Hammoud, Hayma; Bhandage, Amol K.; Koreli, Stasini; Chowdhury, Azazul Islam; Bergsten, Peter; Birnir, Bryndis (Frontiers in Immunology, 2025)
Glucose uptake in activated CD4+ T cells is essential for increased metabolic needs, synthesis of biomolecules and proliferation. Although, facilitated glucose transport is the predominant route for glucose entry at the time of activation, here we demonstrate role for the sodium-dependent glucose transporter SGLT2. By 72 h after activation, SGLT2 is expressed and functional in the human CD4+ T cells. SGLT2 inhibitors, phlorizin and empagliflozin decreased glucose uptake into the human CD4+ T cells compared to untreated cells. Phlorizin (25 μmol/L) reduced glycolysis at 5.6 mmol/L glucose and IFNγ levels at both 5.6 mmol/L and 16.7 mmol/L glucose. In contrast, empagliflozin (0.5 μmol/L) only decreased IFNγ levels in 16.7 mmol/L glucose. GABA enhanced phlorizin inhibition at both 5.6 mmol/L and 16.7 mmol/L glucose in the presence of insulin. Insulin strengthens GABAA receptors signaling in CD4+ T cells. The results are consistent with expression of SGLT2 after activation of human CD4+ T cells, that facilitates concentrating glucose uptake into the cells, enabling enhanced release of inflammatory molecules like IFNγ. Importantly, inhibition of SGLT2 decreases IFNγ release.